The Relationship Between Family Economic Conditions and Children's Educational Interest in Pringgasela District, East Lombok Regency - Bq. Elok Nirwana (ICM Research (Yayasan Insan Cendekia Mandalika), 2026)
This study examines the relationship between family economic conditions and children's educational interest in Pringgasela District, East Lombok Regency, with particular attention to the role of Islamic economic values in sustaining children's motivation to pursue education. Employing a qualitative descriptive approach, data were gathered through in-depth interviews, observations, and documentation involving families, children, and school stakeholders. Analysis followed the stages of data reduction, presentation, and conclusion drawing. Findings reveal that family economic conditions significantly influence children's educational interest: economically stable families are better positioned to provide learning facilities, cover educational expenses, and offer moral support, whereas families with limited resources frequently struggle to meet their children's educational needs, leading to declining motivation to continue schooling. Notably, the study found that the internalization of Islamic economic values within the family particularly trustworthiness (amanah), justice, and responsibility can meaningfully strengthen children's commitment to education despite economic constraints. The study concludes that family economic conditions and children's educational interest are closely interrelated, and that integrating Islamic economic principles into family management offers a viable strategy for sustaining children's enthusiasm for learning, thereby nurturing a generation that is educated, morally grounded, and prepared for future challenges.